The quality of corporate social responsibility (CSR) reporting of Malaysian companies - Mohd Herry, Mohd Nasir (2019)
Malaysia is ranked among the best in the Asian region in terms of corporate social responsibility (CSR) reporting. However, the focus of reporting is more towards compliance of the disclosure requirements rather than the content. More recent studies suggest that CSR reporting should no longer be a matter of disclosure compliance but should shift towards reporting quality issues including the issues of ‘what’ and ‘how’ CSRs are disclosed. Additionally, the existence of CSR practices such as stand-alone reports and CSR guidelines is an impetus for companies in Malaysia to improve the quality of CSR reporting. Hence, taking the perspective of organizational legitimacy theory, this study aims to determine five dimensions of CSR reporting quality and their relationships with CSR practices as adopted by companies in Malaysia. The research design was developed through two phases: content analysis and multivariate analysis. Analyses were conducted on 254 companies listed in the main market of Bursa Malaysia in 2016 from among various industries. The findings show that the overall quality of CSR reporting in Malaysia is still low at around 24 percent. The existence of CSR practices is also seen as having a weak relationship with the quality of CSR reporting. This suggests that the practice of CSR reporting in Malaysia is rather “symbolic”, which purpose is more towards legitimizing the existence of the companies. However, the level of CSR reporting in Malaysia is at its best regarding the dimension of quantity and density. The selection of the CSR reporting theme shows no difference among the industries. Most industries select the workplace theme regardless of the core business, which is contrary to previous studies. The finding is consistent with the institutional theory, which argues that due to mimetic influence, companies in the same industry have the potential to imitate the form of reporting made by larger companies.